Logic Requirement Model of Web Based e-learning in Learning Management System for Features Selection - Narti Prihartini (JEPIN (Jurnal Edukasi dan Penelitian Informatika), 2022)
Requirement engineering phase is logically known to check the compliance of application such in web-based e-learning development. This research indicates that basic aspects of web-based e-learning can be used to identify or elicit the early requirement and classify it into the functional and non-functional approach. The research found that even in learning management system (LMS) Based, some of the web-based e-learning are using for different goals. It is challenging to develop a system of web-based e-learning to get the requirement focus at the early phase and select the feature that can fill the requirement. This study goal is developing a requirement model to describe the web requirement focus and decompose every web requirement aspects through logical modeling. Analysis due to the interaction and coverage of web-based e-learning is combined with web modeling aspects including content, interaction, functional, navigation and configuration to show the relation among detail requirements. Requirements are found in a systematic way by modeling its logic to determine the basic needs in the using of learning management system. The result from this requirement model proves that web-based e-learning requirements are sustain-ably identified to complement each requirements and can be implemented to classify the specific requirement to select the appropriate web-based e-learning features from early phase development.